2019
DOI: 10.1103/physrevb.99.140401
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-photon coupling in the noncollinear magnetic insulator Cu2OSeO3

Abstract: Anticrossing behavior between magnons in a non-collinear chiral magnet Cu2OSeO3 and a twomode X-band microwave resonator was studied in the temperature range 5-100 K. In the fieldinduced ferrimagnetic phase, we observed a strong coupling regime between magnons and two microwave cavity modes with a cooperativity reaching 3600. In the conical phase, cavity modes are dispersively coupled to a fundamental helimagnon mode, and we demonstrate that the magnetic phase diagram of Cu2OSeO3 can be reconstructed from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…It comes from the small mode volume V c ∼ 0.0051 mm 3 for the coplanar resonator and indicates the significance of having a localized and concentrated photon mode volume to reach a strong coupling strength. It is worthwhile to note a few different planar resonator designs such as split-ring [17,39,40] and lumped-element resonators [41,42]. The former allows an optimal filling of thin-film magnetic materials in the resonator, with g/2π close to 1 GHz; the latter has the highest g 0 by further reducing the mode volume.…”
Section: (A)mentioning
confidence: 99%
“…It comes from the small mode volume V c ∼ 0.0051 mm 3 for the coplanar resonator and indicates the significance of having a localized and concentrated photon mode volume to reach a strong coupling strength. It is worthwhile to note a few different planar resonator designs such as split-ring [17,39,40] and lumped-element resonators [41,42]. The former allows an optimal filling of thin-film magnetic materials in the resonator, with g/2π close to 1 GHz; the latter has the highest g 0 by further reducing the mode volume.…”
Section: (A)mentioning
confidence: 99%
“…In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11]. Typically, the material of choice for these experiments is Yttrium Iron Garnet (YIG) due to its low magnonic and photonic loss, and high spin density, however, other ferrimagnetic materials are often considered for study such as lithium ferrite (LiFe) [16] and Cu 2 OSeO 3 [17]. LiFe has been of recent interest for use in hybrid cavitymagnon systems due to is higher spin density when compared to YIG.…”
Section: Introductionmentioning
confidence: 99%
“…For example, either the oscillator or the dissipative third-party can be superconducting qubit [6,23], dielectric nanostructures [24], antiferromagnets [25,26], high-order spin wave modes [27] or other excitations such as phonons [28]. It has been reported recently that magnetic textures can also be coupled with the cavity photons [29,30]. Based on the understanding of dissipative coupling, the nonlinear effect [31,32] and topological properties of exceptional point [33][34][35][36] can be generalized and new physics is expected.…”
mentioning
confidence: 99%